Value System and Resilience in the Management of Rawa Lebak - Rezeky, Shinta Mutiara; Pandjaitan, Nurmala K; Sjaf, Sofyan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
Rawa lebak is the main source of livelihood for the people living around it. Climate change makes it difficult for community to predict the arrival of the rainy season. The community is vulnerable to crop failure. In addition, the existence of regional regulations governing the management of rawa lebak in the flood season increasingly pressured the community. Communities also become vulnerable to food insecurity The purpose of this study is to identify the social values, economic values, and political values of rawa lebak, and to see the resilience of the community to the food insecurity conditions in the rawa lebak area. This research uses qualitative method. Qualitative data is obtained in three ways, observations, indepth interview, and documentations on an ongoing basis. The result of this research is rawa lebak has the social values through various rituals conducted by the community before rice planting season. The economic values of rawa lebak is its function as the main source of livelihood for the community. The political values of rawa lebak is the ownership system of rawa lebak. The community in Tapus Village is still at the level of resilience as stability because it has not been able to perform an optimum adaptive capacity. In addition, the domination of the political value of the rawa lebak makes people less able to make optimum use of the economic value of the swamp swamp. This makes community more sensitive and vulnerable to food insecure.